Avaliação da ictiofauna na região portuária de São Luís caracterização ecológica, pesqueira e contaminação por microplásticos - CARVALHO, Athina da Silva (2024)
The coastalzone plays a keyrole in the development of everyecosystem. It is a highlydynamic environment that is constantly influenced by both anthropogenic and environmental factors. Unfortunately, with growing social and economic demand, this space has been heavily impacted. The implementation of port activities has been one of the most obvious forms of disturbance to the coastal zone, as they can cause impacts such as erosion, siltation, contamination of aquatic environments, among others. The coastal zone is also constantly affected by pollution. Among the solid waste that most contaminates these environments are plastics, which can be found in different sizes in the environment (macro-, meso- and microplastics). Due to their small size, lightness, and color, microplastics can be ingested by a range of aquatic organisms, causing harmful effects. Studies investigating coastal environmentswill contribute to more in-depth discussions on the use and preservation of this ecosystem. In this context, the ichthyofauna stands out as a good indicator, as they respond to changes in theenvironment inwhich they live. Withthis in mind, thisstudyaimed to analyze the ichthyofauna present in the Coqueiros Strait, a coastal environment of great environmental importance for the state of Maranhão. his work was divided into two chapters: The first deals with a characterization of the environment, providing a survey of the diversity and abundance of the ichthyofauna present in the coconut grove. To this end, fish specimens were collected quarterlybetween February and December 2022 at four sampling points. In order to verify the degree ofdisturbance to the environment, an ABC curve was constructed for the months of collection, inaddition to verifying the physical-chemical parameters of the environment. The presence of microplastics in the stomachs of commercial fish was also investigated using sodium hydroxide to dissolve the soft tissue. It was noted that the ichthyofauna present in the study environment is more abundant during the dry season and has an average diversity. The ABC curve showed that the environment studied does not show major disturbances, since the Biomass curve alwaysexceeded the abundance curve. With regard to microplastics, 100% of the samples were contaminated by microplastics, and two forms of microplastics were found: Fibers and fragments, with fibers being the predominant microplastic in all the samples analyzed, fibers were found in blue, black and red coloration and all the fragments found were in blue coloration. The results of this research could contribute to ODS 14, life in the water, which has as its maingoal the reduction of pollution, defense of biodiversity and ecosystems, regulation of fishing, and promotion of marine sciences.